THE ANALYSIS OF MULTIDIMENSIONAL ANOMALOUS DIFFUSION EQUATION - Bambang Hendriya Guswanto (Universitas Jenderal Soedirman, 2018)
We discuss the properties of the fundamental solution of multidimensional anomalous diffusion equation such as symmetric, decay, nonnegative, normality, and bounded in mathematical analysis approach.